2020
DOI: 10.1186/s12904-020-00682-2
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ clinical prediction of survival in head and neck cancer patients in the palliative phase

Abstract: Background The prognosis of patients with incurable head and neck cancer (HNC) is a relevant topic. The mean survival of these patients is 5 months but may vary from weeks to more than 3 years. Discussing the prognosis early in the disease trajectory enables patients to make well-considered end-of-life choices, and contributes to a better quality of life and death. However, physicians often are reluctant to discuss prognosis, partly because of the concern to be inaccurate. This study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…They found that patient prognostic expectations did not change. Another recent prospective study demonstrated that physicians inaccurately overestimate survival in patients with head and neck cancer (Hoesseini et al, 2020). Together with our results, this suggests that currently in follow‐up care patients, aren't being accurately informed about their prognosis and even if they are, it may not change their expectations.…”
Section: Discussionmentioning
confidence: 99%
“…They found that patient prognostic expectations did not change. Another recent prospective study demonstrated that physicians inaccurately overestimate survival in patients with head and neck cancer (Hoesseini et al, 2020). Together with our results, this suggests that currently in follow‐up care patients, aren't being accurately informed about their prognosis and even if they are, it may not change their expectations.…”
Section: Discussionmentioning
confidence: 99%
“…[1] is the most common approach among the three types of CPS: TQ, surprise question (SQ), and probabilistic question (PQ). However, previous studies have reported that CPS is likely to be signi cantly optimistic in estimating patient survival [6,7]. The TQ type of CPS is known to be approximately 20-30% of accuracy compared to the actual survival [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, limiting the speci c time frame has been found to be in uenced the accuracy of PQ. Previously, CPS was known to be inaccurate in preceding studies [7,8,14,15]. However, a recent study showed that CPS was accurate in patients with weeks of survival under palliative care [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that health care providers are not able to accurately forecast cancer patients' life‐expectancy and tend to overestimate survival. 5 , 6 , 7 Over the last years, an internally and externally validated prognostic model named “OncologIQ” has been developed. This model estimates the 1‐ to 10‐year overall survival (OS) chances of patients with primary HNC who are eligible for curative treatment.…”
Section: Introductionmentioning
confidence: 99%